Combination Filtration - Ultraviolet Unit to Reduce the Organic Content and Pathogens of Domestic Wastewater For Clinical Activities - R Novembrianto; Munawar; M A S Jawwad; R H A Murti; W D Lestari; M N Rhomadhoni (Biomedical and Mechanical Engineering Journal (BIOMEJ), 2022)
The rise of clinical activities is one of the health care facilities that have the potential to pollute wastewater on organic compounds and especially pathogenic microorganisms. Technology in reducing organic and pathogenic content using combined ultraviolet filtration in wastewater treatment systems is one the effective method. Filtration uses activated carbon and silica with a variation of the ratio 2:3 and 3:2, while ultraviolet use a power variation of 9 watts and 15 watts. The results obtained are the best composition from the filtration process, which is a ratio of 2: 3 with the ultraviolet process using 15 watts using an exposure time of 5 hours with the remaining total coliform as much as 200 MPN/100mL. The results of this research have complied with the quality standards.